2012
DOI: 10.1111/j.1365-313x.2011.04886.x
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco NtLTP1, a glandular‐specific lipid transfer protein, is required for lipid secretion from glandular trichomes

Abstract: SUMMARYGlandular trichomes are the phytochemical factories of plants, and they secrete a wide range of commercially important natural products such as lipids, terpenes and flavonoids. Herein, we report that the Nicotiana tabacum LTP1 (NtLTP1) gene, which is specifically expressed in long glandular trichomes, plays a role in lipid secretion from trichome heads. NtLTP1 mRNA is abundantly transcribed in trichomes, but NtLTP3, NtLTP4 and NtLTP5 are not. In situ hybridization revealed that NtLTP1 mRNAs accumulate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 52 publications
2
78
0
1
Order By: Relevance
“…In plants, LTPs have recently been shown to function in the export of wax lipids and diterpenes from the plasma membrane, across the cell wall, to the cuticle [71][72][73][74]. Given that LTPs generally lack substrate specificity, it is possible that the same LTPs may also be transporting VOCs to neighboring cells, intercellular spaces (in some cases for release via stomata), or the cuticle.…”
Section: Cell Wallmentioning
confidence: 98%
“…In plants, LTPs have recently been shown to function in the export of wax lipids and diterpenes from the plasma membrane, across the cell wall, to the cuticle [71][72][73][74]. Given that LTPs generally lack substrate specificity, it is possible that the same LTPs may also be transporting VOCs to neighboring cells, intercellular spaces (in some cases for release via stomata), or the cuticle.…”
Section: Cell Wallmentioning
confidence: 98%
“…In addition to trichome-specific EST resources, numerous glandular trichome-specific gene promoters have been reported in the literature for a variety of plants, including (but not restricted to) Antirrhinum majus, A. annua, C. sativus, H. lupulus, Mentha spp., N. tabacum, S. lycopersicum, and S. habrochaites (Okada and Ito, 2001;Wang et al, 2002Wang et al, , 2011Wang et al, , 2013Gutiérrez-Alcalá et al, 2005;Liu et al, 2006;Jaffé et al, 2007;Kim et al, 2008;Shangguan et al, 2008;Ennajdaoui et al, 2010;Choi et al, 2012;Sallaud et al, 2012;Spyropoulou et al, 2014;Kortbeek et al, 2016;Laterre et al, 2017;Vining et al, 2017;for review, see Tissier, 2012b). It is worth noting that most of these trichome-specific promoters are active in mature glandular trichomes (mostly in glandular cells at the tip of the trichome).…”
Section: A Detailed Understanding Of Glandular Trichome Initiation Anmentioning
confidence: 99%
“…The OsLTP110 protein could inhibit the germination of Pyricularia oryzae spores in vitro (Ge et al, 2003) and overexpression of the LTP gene could bring a substantial resistance to biotic stresses. For instance, transgenic tobacco overexpressing either the TaLTP3F1, HvLTP2 (Hordeum vulgare) and NtLTP1 (Nicotiana tabacum) genes showed fungal, bacterial and aphid resistance, respectively (Choi et al, 2012;Kirubakaran et al, 2008;Molina and García-Olmedo, 2003). In addition, nsLTP genes could respond to abiotic stresses including NaCl, drought, cold and wounding (Cameron et al, 2006;Torres-Schumann et al, 1992;Yubero-Serrano et al, 2003), and recently it has been shown that ZmLTP3 and AtLTP3 could improve plant survival under salt and drought stresses, respectively (Guo et al, 2013;Zou et al, 2013).…”
Section: Introductionmentioning
confidence: 97%